2021
DOI: 10.1136/svn-2020-000693
|View full text |Cite
|
Sign up to set email alerts
|

Role of depressive symptoms in cardiometabolic diseases and subsequent transitions to all-cause mortality: an application of multistate models in a prospective cohort study

Abstract: Background and purposeThe role of depression in the development and outcome of cardiometabolic diseases remains to be clarified. We aimed to examine the extent to which depressive symptoms affect the transitions from healthy to diabetes, stroke, heart disease and subsequent all-cause mortality in a middle-aged and elderly European population.MethodsA total of 78 212 individuals aged ≥50 years from the Survey of Health Ageing and Retirement in Europe were included. Participants with any baseline cardiometabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…In individuals with LLD, the SASP index was most strongly associated with the cardiovascular and cardiometabolic health factor. Previous studies have demonstrated a robust bidirectional relationship between LLD and physical health 6 and the mediating effect of medical conditions on treatment outcomes 45 . One previous study in young and middle-aged adults with major depressive disorder demonstrated that the SASP index was most strongly correlated to BMI 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with LLD, the SASP index was most strongly associated with the cardiovascular and cardiometabolic health factor. Previous studies have demonstrated a robust bidirectional relationship between LLD and physical health 6 and the mediating effect of medical conditions on treatment outcomes 45 . One previous study in young and middle-aged adults with major depressive disorder demonstrated that the SASP index was most strongly correlated to BMI 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when the accurate onset time of some diabetes patients was unavailable, we approximated the onset time using the midpoint time. Although this method has been adopted by many studies [41,42], the accuracy of the onset time could not be fully guaranteed and the measurement error might be introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study show that between 14·6% and 22·4% of individuals with diabetes had depression depending on the method used to assess it. High prevalence estimates can be expected, since on the one hand, there is evidence that depression is a risk factor for diabetes and, on the other hand, studies show that the distress caused by diabetes contributes to the development of depression [ 1 , 8 , 33 36 ]. The results of our study are within the range of findings from the two most recent meta-analyses on depression among persons with diabetes where prevalence ranged from 1·8% up to 88·0% [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%